x=ay
y=x+10
so
x=a(x+10)
x=ax+10a
x-ax=10a
x(1-a)=10a
x=(10a)/(1-a)
x=ay
y=x+10
plugging it in x= a(x+10)
the book SAYS solving for x yields x= 10a/(1-a)
for the life of me I can't see how they got that.
I tried multiplying by its reciprocal, working around it.... I just cant see it for the life of me.
the book's solution doesn't show this step. is there something really basic I'm overlooking?
oh wow that was so simple I can't believe it.
do you guys have any tips on trying to catch obvious things like that?
I'm so oblivious sometimes, but I have a study sheet and go over the rules every day. I just manage to overlook them somehow...
thanks for the help, by the way